Analisis Level Metakognisi Siswa Sekolah Menengah Atas Penghafal al-Qur’an dalam Memecahkan Masalah Matematika - Dewi Rosikhoh; Liny Mardhiyatirrahmah; Abdussakir Abdussakir (Institut Agama Islam Negeri Curup, 2019)
Metacognition has a key position on problem solving in mathematics. Metacognition is thinking about what they think. This research is qualitative research purposing for identifying of students’ metacognition level on matematics problem solving based on their quatity juzs of Qur’an memorized. The subjects of this research is three students who are in 12th grade in Senior High School. Students’ metacognition level is identified through test and indicator of metacognition level. The result of research show that metacognition level of Senior High School students taking in level of aware use, semi strategic use and semi reflective use. The student who has less than 10 juzs in Qur’an memorized is in aware use level. The student who has 10 until less than 20 juzs in Qur’an memorized is in semi strategic use level. The student who has 20 until 30 juzs in Qur’an memorizing is in semi reflective use level. Based on this reasearch, researchers conclude that the more juzs memorized, the higher level that students get.